Functional Role of Natriuretic Peptides in Risk Assessment and Prognosis of Patients with Mitral Regurgitation - Giovanna Gallo (Journal of Clinical Medicine, 2020)
The management of mitral valve regurgitation (MR), a common valve disease, represents a challenge in clinical practice, since the indication for either surgical or percutaneous valve replacement or repair are guided by symptoms and by echocardiographic parameters which are not always feasible. In this complex scenario, the use of natriuretic peptide (NP) levels would serve as an additive diagnostic and prognostic tool. These biomarkers contribute to monitoring the progression of the valve disease, even before the development of hemodynamic consequences in a preclinical stage of myocardial damage. They may contribute to more accurate risk stratification by identifying patients who are more likely to experience death from cardiovascular causes, heart failure, and cardiac hospitalizations, thus requiring surgical management rather than a conservative approach. This article provides a comprehensive overview of the available evidence on the role of NPs in the management, risk evaluation, and prognostic assessment of patients with MR both before and after surgical or percutaneous valve repair. Despite largely positive evidence, a series of controversial findings exist on this relevant topic. Recent clinical trials failed to assess the role of NPs following the interventional procedure. Future larger studies are required to enable the introduction of NP levels into the guidelines for the management of MR.